Analisis Sistem Kearsipan Di Tutorping Lembaga Ketahanan Nasional RI - Ni Made Puspita Dewi; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
This research uses a qualitative descriptive method, namely by analyzing and describing the problems found. This research is based on primary data and secondary data. Primary data in this research was obtained using data collection techniques in the form of observation, interviews, and documentation. Secondary data was obtained from books, previous research, and articles related to research related to archival systems. The samples from this research were Tutorping employees of the Indonesian National Resilience Institute. Researchers also used data collection techniques in the form of surveys sent to 20 employees. In companies and institutions, the archival system is planning, supervising, training, organizing, developing, and managerial activities oriented towards the creation, maintenance, use, and depreciation of archives. This research aims to determine the archiving system at Tutorping, the Indonesian National Resilience Institute. The results of this research show that the majority of employees stated that they had implemented the archiving system well, and the archival storage system had been carried out by the needs of the activities that had been determined, but the space and space were inadequate so that the records piled up, but within a certain period they were destroyed following procedures. In the context of effectiveness, a good level of understanding of the archive system can create improvements in employee work. This research provides insight for employees into the importance of understanding the archive system within the institution. In this way, there will be an improvement in the archive system in the institution as a whole.